PENGARUH AI GEMINI TERHADAP SELF-EFFICACY MATEMATIS SISWA SMK - Syarifah Mahdiyah; Ririn Dwi Agustin (Universitas Teknokrat Indonesia, 2026)
This study aims to determine the effect of mathematics learning assisted by Artificial Intelligence using AI Gemini on students’ mathematical self-efficacy in vocational high schools. This study contributes novelty by specifically examining the use of AI Gemini as an instructional support tool to improve mathematical self-efficacy among vocational high school students, a topic that has received limited attention in previous studies. The study employed a quantitative approach with a quasi experiment design using a posttest-only control group design. Participants consisted of 30 students divided into an experimental class and a control class. The experimental class received mathematics learning assisted by AI Gemini, while the control class received conventional learning without AI assistance. The research instrument used a mathematical self-efficacy questionnaire with a Likert scale adapted from Usher and Pajares. Data analysis employed descriptive statistics and an independent sample t-test using SPSS. The findings showed that students in the experimental class achieved higher mathematical self-efficacy scores than those in the control class. The experimental class obtained an average score of 53.60, while the control class obtained 32.20. The independent sample t-test results indicated a significance value below 0.05, demonstrating that mathematics learning assisted by Artificial Intelligence significantly affected students’ mathematical self-efficacy. AI Gemini supported students in obtaining a more interactive, flexible, and responsive learning experience, thereby strengthening confidence in mathematics learning.